2015
DOI: 10.1002/14651858.cd011320.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Time-lapse systems for embryo incubation and assessment in assisted reproduction

Abstract: There is insufficient evidence of differences in live birth, miscarriage, stillbirth or clinical pregnancy to choose between TLS and conventional incubation. Further data explicitly comparing the incubation environment, the algorithm for embryo selection, or both, are required before recommendations for a change of routine practice can be justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
132
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 170 publications
(137 citation statements)
references
References 13 publications
2
132
0
3
Order By: Relevance
“…Our opinion is similar to some recently published systematic reviews and opinions [9,30,31]: we believe that the available evidence is insufficient to support the use of time-lapse compared with conventional evaluation for embryo selection. Future trials examining time-lapse are necessary and should be encouraged.…”
Section: Discussionsupporting
confidence: 77%
“…Our opinion is similar to some recently published systematic reviews and opinions [9,30,31]: we believe that the available evidence is insufficient to support the use of time-lapse compared with conventional evaluation for embryo selection. Future trials examining time-lapse are necessary and should be encouraged.…”
Section: Discussionsupporting
confidence: 77%
“…Those reports demonstrated that morphokinetic evaluation by time-lapse imaging can provide a more comprehensive and detailed analysis of the developmental events than that of static evaluation and thus may assist in selecting top quality embryos for transfer. Other studies, however, have questioned the benefit of the time-lapse system over the traditional incubators and assessment grading systems [24][25][26][27][28][29].…”
Section: % Of All Biopsy Procedures Performed In Europe Betweenmentioning
confidence: 99%
“…Morphologic criteria to grade embryos correlate poorly with pregnancy and live birth rates and fail to identify chromosomally normal embryos [5][6][7]. The utilization of time-lapse embryo growth monitoring systems has also gained popularity, but data convincingly demonstrating improved outcomes as a result of this technology is still lacking [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%